Strain-engineering tunable electron mobility of monolayer IV–V group compounds. Issue 35 (29th August 2018) - Zhang, Wei; Yin, Jiuren; Ding, Yanhuai; Jiang, Yong; Zhang, Ping
Abstract : First-principles simulations demonstrate the anisotropic and high mobility in the new group monolayer IV–V semiconductors. Abstract : First-principles simulations demonstrate the anisotropic and high mobility in the new group monolayer IV–V semiconductors. The strain-engineered bandstructure reveals the conduction bands are sensitive to armchair-direction deformation. By applying strains, the electrical transportation in the armchair direction can be further improved or deteriorated. We use this important feature to achieve the tunable electron mobility in monolayer IV–V semiconductors. The controllable introduction of strain into semiconductors offers an important degree of flexibility in electrical transportation. Meanwhile, our works leads to a new approaches for research on mobility control in two-dimensional semiconductors. These will be useful for novel mechanical-electronic devices related to mobility switching.